The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17811/ebl.6.2.2017.48-53
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Market Hypothesis: Evidence from three centuries of UK data

Abstract: We examine the evolving efficiency of UK stock market and currency (British Pound) during the last three centuries. Using both Automatic Variance Ratio (AVR) and Automatic Portmanteau (AQ) tests, we find evidence of time-varying degree of efficiency which supports the Adaptive Markets Hypothesis (AMH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The calculations showed that the green bond market is not effective even in a weak form at the moment. This is consistent with the conclusions drawn from other segments of the stock exchanges ( [3][4]6]). At the same time, this study confirms: the classic calendar effects, massively manifested in the middle of the 20th century, are not typical for green bonds and for most other securities [7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The calculations showed that the green bond market is not effective even in a weak form at the moment. This is consistent with the conclusions drawn from other segments of the stock exchanges ( [3][4]6]). At the same time, this study confirms: the classic calendar effects, massively manifested in the middle of the 20th century, are not typical for green bonds and for most other securities [7].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it should be borne in mind that empirical data do not confirm the rationality of investor behavior, their exclusive orientation to future income. Investors may succumb to herd instinct, draw incorrect conclusions about losses or gains [4], as well as loss aversion or overconfidence are characteristic of many investors [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The AMH hypothesis for the British pound in short and long-spans of data has also been confirmed byCharles et al (2012) andAlmail and Almudhaf, (2017) respectively.Journal of Economics and BehavioralStudies (ISSN: 2220-6140)Vol. 11, No.…”
mentioning
confidence: 65%
“…In light of the importance of currency markets, efficiency of the same has been examined extensively, since the seminal work of Meese and Rogoff, (1983), with the widespread acceptance that it is difficult to beat the random walk model in predicting the conditional mean dynamics of foreign exchange rate changes (see for example, Chung and Hong, (2007), Charles et al, (2012), Plakandaras et al, (2013Plakandaras et al, ( , 2015a, Balcilar et al, (2016), Papadimitriou et al, (2016), Almail and Almudhaf (2017), and Christou et al, (forthcoming) for detailed reviews of this literature). However, the majority of these studies are based on the tests of some forecast models or forecast rules, i.e., these works examine the efficiency of models rather than data, and as a result, the conclusions are dependent on the model used.…”
Section: Introductionmentioning
confidence: 99%
“…Recent debate on energy studies centers on prediction or forecasting of energy prices, methodological and data mining with few studies on efficiency. Similarly, bulk of the studies on energy efficiency focuses on electricity (Charles et al, 2017); (Almail and Almudhaf, 2017); (Ramírez et al, 2015); (Mcgregor, 2017) alternative sources of energy (Apergis and Vouzavalis, 2018); (Ready, 2018); (Shah et al, 2018); (Huang et al, 2018); (Polanco et al, 2018); (Safari and Davallou, 2018); (Cuestas and Gil-Alana, 2018) disaggregated energy sources. A few others focused on the effect of energy shocks on macroeconomic variables for instance (Volkov and Yuhn, 2016) examined the effects of oil price shocks on exchange rate fluctuation in five major oil-export economics of Russia, Brazil, Mexico, Canada and Norway and observed that the asymmetric behavior of exchange rate volatility in the studied economies is essentially driven by the efficiency of financial markets rather than the impact of oil proceeds in studied economy.…”
Section: Literature Reviewmentioning
confidence: 99%